A Nyugat-dunántúli régió – régió? - Szörényiné Kukorelli, Irén (Tér és Társadalom, 1998)
By the passing of the 1996 Act on Territorial Development and Management, the legal framework for regional development was established in Hungary. This law provided great chances for the beginning of real regional development in Hungary. The Western Hungarian Region was created by the consent of three counties, Győr- Sopron-Moson, Vas and Zala in May 1997. The newly-established region, however, lacked a common historical memory, moreover there was no modern regional identity on which an organic regional development programme could be based on. Before the official launching of the Western Hungarian Region, by interviewing some of the local mayors of the region, we were trying to fmd out that the cooperation of which counties may constitute a real region. The findings do not fully support the cooperation of the above-mentioned three counties. The reasons for region-building based on this 3-county structure are various, however the fact that these counties are the beneficiaries of the PHARE CBC programme seems to be one of the most important reasons. The Western Hungarian Region according to the legal standards of the 1996 Act is a functional region having no permanent seat, elected assembly and independent budget. The study attempts to highlight the fact that these counties have already had the experience of cross-border regional cooperation in the framework of various international projects such as the Alps-Adriatic Community and The Austrian-Hungarian Cross-Border Council since the mid-1980s. In order to create a „real region" with strong identity and significant economic potential in Western Hungary, there must be a conscious regional policy both at the national and county-level to set up a regional economic network. Naturally, to achieve these goals, these projects should be provided with the necessary financial resources.